IBM SCREEN PRINTING AND OFFSET BUSINESS RIZKY, WELDING WORKSHOP JAYA MAKMUR IN THE VILLAGE SEMANDING DAU MALANG DISTRICT - Jati, Ahmad Waluya (Studi Kasus Inovasi Ekonomi, 2016)
Community Service Program Internal entitledIbm Screen Printing And Offset Business Rizky,Welding Work-shop Jaya Makmur In The VillageSemanding Dau Malang District this is done withthe aim of increasing knowledge of entrepreneurs inthe fields of marketing, design and significance of thefinancial statements and the preparation of financialstatements, in order to improve Entrepreneursbusiness develo-pment.Methods of execution in this devotion is in theform of counseling, training and mentoring.Counseling is done to increase awareness and knowledge partner in the field of marketing, especiallyonline marketing. Further training and mentoringdone to train part-ners and assisting in thepreparation of financial statements partners. As forthe design of training we can only suggest to thecourse design program.Based on the discussions, review ofdocuments and interviews with Mr. Sulianto, themarketing system of prin-ting and screen printing aswell as tradi-tional and welding shop is still limitedto Malang, Surabaya, Jember, Banyuwangi andBanjarmasin. Next implementation team working oncreating a broader mar-keting models using theonline system, but it can not be applied because oflimited physical resources and human resources. Sothat the marketing system can not continue to usemarketing system is offered, as well as for programdesign there is also a shortage of human resources.Based on the results of this activity, it can besaid that the SME screen printing and offsetworkshop and Las potential to be developed further,although it is still managed by the management isvery simple, but from the aspect of management canbe said is good. From the marketing aspects ofexisting resources still have a problem in the masteryof technology, as well as from the production aspectwhen designing an employee is not able to design hisown, Mr. Sulianto it is evident that PITT design stilluse the services of design as a subscription to workof the subscription order. This conclusion is drawnwhen the team offered to sell the online system andoffers courses for its employees. While aspects ofpreparedness of the financial statements can be saidof business printing / screen printing and weldingshop is able to understand what we have given in thetraining preparation of financial statements, and toimplement it in the year 2016.Financial reporting system offered andapplied to Business screen printing and offset Rizkyas well as forge welding Jaya Makmur has beenprepared and can be applied in accordance with thedata source, human resources and existing facilities.Operation is very easy and can generate outputaccurate financial state-ments. Mentoring is doneseveral times to do the training and mentoring of thefinancial reporting system applications.Of the three proposals offered to the partnerthat is an online marketing system, design programand preparation of financial statements, but iscurrently only able to provide one single solution,namely the preparation of financial statements